Characterization of Escherichia coli outer membrane vesicles and the impact of pathogenic ones on NLR signaling pathways - Roghayeh Mohammadzadeh; Ava Behrouzi; Farzam Vaziri; Seyed Davar Siadat (Iranian Journal of Microbiology)
Background and Objectives: The secretion of outer membrane vesicles (OMVs) is a universal event among bacteria. In this study, we characterized OMVs from pathogenic and non-pathogenic strains of Escherichia coli and assessed the effect of pathogenic OMVs on NLR signaling pathways. Materials and Methods: OMVs were extracted by differential centrifugation and characterized by scanning electron microscopy (SEM), SDS-PAGE, Limulus amebocyte lysate (LAL) test, and nucleic acid extraction. Then, the Caco-2 cells were treated with the pathogenic OMVs to evaluate their effect on NLR signaling pathways. Results: SEM showed that pathogenic and non-pathogenic strains produced OMVs in the range of 9-72.9 and 45-270 nm, respectively. The SDS-PAGE revealed that both OMVs had protein bands ranging from 25 to 100 kDa. The LAL test displayed that the concentration of LPS was 2.368 and 0.055 EU/ml in pathogenic and non-pathogenic OMVs, respectively. The evaluation of nucleic acid contents showed no significant difference between both types of OMVs. The assessment of pathogenic OMVs' effect on NLR genes demonstrated that the expression level was changed in some genes. Conclusion: The characterization of OMVs showed that both strains of E. coli secrete OMVs in different sizes and contents. Besides, it was revealed that OMVs can regulate gene expression.